Analyzing special needs reports for children: sociodemographic trends, diagnoses, and support areas over five years (2019–2024) - Canpolat, Semih; Parlak, Mehmet Emin; Kurt Canpolat, Esra; Oz, Erdogan (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to evaluate the special needs reports for children (SNRC) in terms of sociodemographic characteristics, diagnoses, and areas of special needs in the five years from 2019, when special health boards for children were established with the new diagnostic and evaluation criteria.MethodsThis descriptive study was conducted by retrospectively reviewing the board evaluation reports of children aged 0–18 years who applied to Batman Training and Research Hospital SNRC Health Board between March 2019 and March 2024. The study included 420 children for whom all the data in the evaluation reports could be accessed. All data of the participants were collected and analyzed through the Hospital Information Management System (HIMS).ResultsThe mean age at the time of health board admission was 7.41 years with 58.3% boys and 41.7% girls. When the level of special needs was analyzed, the highest rate of 47.1% was found to have Special Condition Requirement Needs (SCRN). The most common reason for application in both boys (68.6%) and girls (64%) was to benefit from Disability Rights. In terms of the distribution of disease areas, the highest rate was in the Cognitive Development Area with 36.2%, the second highest rate was in the Movement Development Area with 27.1%, and the lowest rates were in the Genitourinary System - Surgery Area with 0.2% and in the Hematology-Oncology Area with 0.2%. When the areas of Specific Learning Disabilities (SLD) were analyzed, it was determined that the highest rate was in the area of rehabilitation/early support (intervention) requirement to support cognitive functions with 43.1%. When the special needs levels were analyzed according to the disease areas, the highest rate was found in 13 areas except for the Nephrology area and Genitourinary System-Surgery Area was SCRN. In Nephrology, the rates were equally shared between SCRN and Significant special needs (SSPD) at 50%, while the highest rate in the Genitourinary System-Surgery Field was Special needs (SEN) with 60.6%.ConclusionOur research emphasizes the crucial role of SNRC health board reports in tackling the pressing challenges faced by children and their families. Through harnessing these reports, we can make significant progress in identifying and supporting children with special needs, ultimately enhancing their quality of life. Our findings emphasize the influence of gender and the typical age of 7–8 years for initial evaluation. Looking ahead, it is vital to develop comprehensive strategies to raise community awareness and equip healthcare professionals with the necessary tools to optimize support systems. Through ongoing analysis and adaptation, these efforts hold the promise of fostering a more inclusive and supportive environment for children with diverse needs.